2001
DOI: 10.1080/080352501750064860
|View full text |Cite
|
Sign up to set email alerts
|

The Paediatric Asthma Caregiver’s Quality of Life Questionnaire in Swedish parents

Abstract: With the Paediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ), parents grade impaired activities (5 items) and emotional concern (8 items) from 1 to 7 regarding how much their own quality of life (QoL) has been affected by the disease of their child during the last week. The questionnaire was translated into Swedish. To test the feasibility and validity of the Swedish version, 71 asthmatic children and their families were approached. Sixty-one families (86%) participated. The mean age of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In the same manner, as reported by Juniper et al in the study in which they developed and evaluated the measurement properties of the PACQLQ, our findings provides additional support for adequate test–retest reliability and sensitivity to change of the questionnaire. Consistent with findings by Reichenberg et al [27], we found that the Spanish version of the PACQLQ had good internal consistency and excellent usability, with a very good acceptance by the parents/caregivers of the asthmatic children included in the study. Some previous studies have compared pulmonary function tests measures with PACQLQ scores, although not all with the objective of evaluating the measurements properties of the questionnaire.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the same manner, as reported by Juniper et al in the study in which they developed and evaluated the measurement properties of the PACQLQ, our findings provides additional support for adequate test–retest reliability and sensitivity to change of the questionnaire. Consistent with findings by Reichenberg et al [27], we found that the Spanish version of the PACQLQ had good internal consistency and excellent usability, with a very good acceptance by the parents/caregivers of the asthmatic children included in the study. Some previous studies have compared pulmonary function tests measures with PACQLQ scores, although not all with the objective of evaluating the measurements properties of the questionnaire.…”
Section: Discussionsupporting
confidence: 91%
“…Some previous studies have compared pulmonary function tests measures with PACQLQ scores, although not all with the objective of evaluating the measurements properties of the questionnaire. While some studies have correlated PACQLQ scores with forced expiratory volume in one second (FEV1) and peak expiratory flow rate (PEFR) measures [11,12], others have correlated PACQLQ scores only with PEFR measures [27] and others have correlated PACQLQ scores only with FEV1 measures [28]. With a few exceptions, these studies have shown no significant correlations between PACQLQ scores and changes in FEV1 or PEFR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, being a parent of a child with a chronic condition can negatively affect Health-Related Quality of Life (HRQOL), and each disease presents unique challenges [ 10 ]. For example, parents of asthmatic children have poor HRQOL - especially in the emotional domain, affecting their social life [ 11 ]. Further, mothers, but not fathers, of children with autism spectrum disorders have reported impaired HRQOL, and there is a relationship between maternal well-being and child behaviour characteristics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%